The Development of Appropriate Model and Network Management Method for Thailand: A Case Study of Networks within the Ministry of Social Development and Human Society - Anuwong, Krittiya; Vajirakachorn, Surasit (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This study had three objectives, including; 1) to study the history, structure, operation, problems and obstructions of each form of networks affiliated with Ministry of Social Development and Human Security, 2) to study the form and method in network management of Ministry of Social Development and Human Security, and 3) to suggest the appropriate model and method in network management for Thailand. The data was collected by using in-depth interview from 10 quality networks, including 33 key-informants and also using data from academic documents, books, theses, research papers and other kind of research works. It was found that among 10 quality networks, there were three models of structure and management method, that were; 1) the integrated networks which created directly from the Ministry of Social Development and Human Security and the Social Development and Human Security Provincial Office, 2) the integrated networks which created by other public government organizations, and 3) the integrated networks which created by private sector. Moreover, the study suggested the appropriate model and method in network management for Thailand, by adapted the integration network management model in order to suggest the appropriated ways to improve roles, structure, and working processes of public organization in the area of operation and sharing resources between public, private, and civil society.